A phase-field model with irradiation-enhanced diffusion for constituent redistribution in U-10wt%Zr metallic fuels - Wen, Chunyang; Liu, Wenbo; Yun, Di; Qian, Zhengyu (Frontiers in Materials, 2022)
Constituent redistribution is a unique phenomenon to metal fuels that threatens the safety of such fuel forms. Therefore, it is imperative to establish models to understand the intrinsic mechanisms and predict the redistribution kinetics. In this work, we derived the conservative field equations of the phase-field model from near-equilibrium thermodynamic theory. A macroscopic constituent redistribution phase-field model was developed by introducing the effect of irradiation on the atom mobility and the effect of temperature on the interface mobility. An expression of phase boundary width, applicable to both microscopic and macroscopic scenarios was proposed. The interfacial parameters of the model and the Zr concentration distribution near the fuel surface were discussed at last. These works may help understand constituent redistribution characteristics and promote the application of the phase-field method in studying constituent redistribution in macroscopic scenarios.